Repurposing cabozantinib to GISTs: Overcoming multiple imatinib-resistant cKIT mutations including gatekeeper and activation loop mutants in GISTs preclinical models. (10th April 2019) - Lu, Tingting; Chen, Cheng; Wang, Aoli; Jiang, Zongru; Qi, Ziping; Hu, Zhenquan; Hu, Chen; Liu, Feiyang; Wang, Wenliang; Wu, Hong; Wang, Beilei; Wang, Li; et al.
Abstract: Despite of the great success of imatinib as the first-line treatment for GISTs, the majority of patients will develop drug-acquired resistance due to secondary mutations in the cKIT kinase. Sunitinib and regorafenib have been approved as the second and third line therapies to overcome some of these drug-resistance mutations; however, their limited clinical response, toxicity and resistance of the activation loop mutants still makes new therapies bearing different cKIT mutants activity spectrum profile highly demanded. Through a drug repositioning approach, we found that cabozantinib exhibited higher potency than imatinib against primary gain-of-function mutations of cKIT. Moreover, cabozantinib was able to overcome cKIT gatekeeper T670I mutation and the activation loop mutations that are resistant to imatinib or sunitinib. Cabozantinib demonstrated good efficacy in vitro and in vivo in the cKIT mutant-driven preclinical models of GISTs while displaying a long-lasting effect after treatment withdrawal. Furthermore, it also exhibited dose-dependent anti-proliferative efficacy in the GIST patient derived primary cells. Considering clinical safety and PK profile of cabozantinib, this report provides the basis for the future clinical applications of cabozantinib as an alternative anti-GISTs therapy in precision medicine. Highlights: Cabozantinib overcomes imatinib resistant cKIT gatekeeper T670I mutant. Cabozantinib overcomes imatinib or sunitinib resistant cKIT activation loop mutants. Cabozantinib displays great efficacies in GISTs preclinical in vivo models. Cabozantinib displays long-lasting response after treatment withdrawal. Cabozantinib inhibits the growth of human GISTs patient-derived primary cells.